Laser Emissions from Disodium Fluorescein-Doped Poly(Vinyl Alcohol) Films - Yap, Seong-Shan; Tou, Teck-Yong; Ng, Seik-Weng (The Japan Society of Applied Physics, 2000)
Superradiant-mode laser emissions were obtained from disodium fluorescein (DF)-doped poly(vinyl alcohol) (PVA) films which had been dip-coated on a microscope glass slide. When the film was transversely pumped using a nitrogen laser, superradiant emission was trapped and propagated in the supporting glass slide which acted as a waveguide. The trapped light underwent multiple internal reflections before it exited at both ends of the slide, producing a lasing effect. The laser beam profile varied with the edge condition of the glass slide; a circular beam was obtained with a frosted edge. An output conversion efficiency of 22% was obtained for a fresh sample while its lasing output energy at a localized excitation position, or operating lifetime, decreased at a rate of 0.015% per shot of nitrogen laser. Despite the decrease in output energy, the laser peak wavelength of DF was largely unchanged.